DESAIN RANGKA ATAP PERPUSTAKAAN BANJAR WIJAYA - Dewi Linggasari; Vincentius Felix; Kezia D. Khovi Br Tarigan; Gratia Verara Vici (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The Civil Engineering Undergraduate Study Program and the Tarumanagara University Research and Community Service Institute in collaboration with residents of RW 07 Banjar Wijaya, Cipete sub-district, Tangerang City, presented a library building, hereinafter referred to as Banjar Wijaya People's Reading Park. The reading garden is a place that is needed by the community around the location as a place to get information, knowledge and a place for refreshing. In the construction of the library around the reading garden, the local community experienced difficulties in planning a roof truss made of steel. The Civil Engineering Undergraduate Study Program and the Institute for Research and Community Service of Tarumanagara University in collaboration with residents of RW07 Banjar Wijaya, Cipete sub-district, Tangerang City, presented a lightweight steel roof truss design for the library building built in the Greek Cluster environment. Mild steel is a material made of steel with a much lower carbon content, thinner and lighter than conventional steel. When compared to wood as a roof truss, mild steel is cheaper and easier to install but still has good sturdiness. Mild steel on the surface is coated with galvanized cells so that it is not easy to rust, is resistant to various weather conditions and is able to support the geting or arbes load it carries. The lightweight steel roof truss is able to protect the library building to the maximum.